Strength and Porosity of Porous Concrete Pavement Containing Nano Black Rice Husk Ash - Putra Jaya, Ramadhansyah; K. A., Masri; S. A., Mangi; M. I., Mohd Yusak; Nordiana, Mashros; Muhammad Naqiuddin, Mohd Warid; M. K. I. M., Satar; W. I., Mohd Haziman (IOP Publishing, 2020)
Rice husk ash (RHA) as replacement material in the conventional concrete mixture has been widely studying around the world. However, there is a lack of study on nanoparticle produced from black rice husk ash (BRHA) used as a replacement material in porous concrete pavement mixture. Therefore, this study aims to evaluate the performance of porous concrete pavement containing nano black rice husk ash in terms of compressive strength, porosity and its correlation. A nano BRHA dosage of 10, 20, 30 and 40% by weight of binder was used throughout the experiments. Four different grindings of BRHA were examined, and it was found that BRHA ground had a nanoparticle between 64 nm to 85 nm. There appears to be an optimum replacement of approximately 10% nano BRHA, during which time the compressive strength and porosity increase significantly.